1994
DOI: 10.1007/bf01703437
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and nucleotide sequence of the coat protein gene of a Cuban isolate of potato leafroll virus and its expression inEscherichia coli

Abstract: Total RNA from infected Physalis floridana was isolated to generate complementary DNA corresponding to the coat protein (GP) gene of a Cuban isolate of potato leaf roll virus (PLRV). This cDNA was amplified by the polymerase chain reaction (PCR) and cloned into the bacterial expression vectors pEX(1-3) for fusion protein expression in E. coli. The product was detected by antibodies specific for the PLRV CP. The coding sequence of the CP gene was determined, and the predicted length of the CP was 208 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Another isolate from Poland (PLRV-P) is also more closely related to the three former isolates than to the latter (Palucha et al ., 1994 ). Similarly, sequencing of ORF3 of Cuban and Brazilian isolates suggests that these isolates are more closely related to the Northern temperate country isolates than to the Australian isolate (López et al ., 1994 ; Caram de Souza-Dias et al ., 1999 ). Finally, comparison of ORF3 and ORF5 sequences between Scottish isolates has shown that these isolates are as divergent from each other as they are from overseas isolates, except for the one from Australia (Jolly & Mayo, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another isolate from Poland (PLRV-P) is also more closely related to the three former isolates than to the latter (Palucha et al ., 1994 ). Similarly, sequencing of ORF3 of Cuban and Brazilian isolates suggests that these isolates are more closely related to the Northern temperate country isolates than to the Australian isolate (López et al ., 1994 ; Caram de Souza-Dias et al ., 1999 ). Finally, comparison of ORF3 and ORF5 sequences between Scottish isolates has shown that these isolates are as divergent from each other as they are from overseas isolates, except for the one from Australia (Jolly & Mayo, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme‐linked immunosorbent assay (ELISA) is a common technique for detecting PLRV in infected plants (Casper, 1977; Clarke, 1981). Reverse transcription‐polymerase chain reaction (RT‐PCR) using PLRV‐specific primers and sequencing have been also developed for detection and classification of the viral isolates (López et al., 1994; Djilani Khouadja et al., 2003; Mukherjee et al., 2003). We have used double‐antibody sandwich‐enzyme‐linked immunosorbent assay (DAS‐ELISA) to assess the incidence of PLRV infection in potatoes in four Iranian Provinces.…”
Section: Introductionmentioning
confidence: 99%